مقاربات تاريخية لتطور الشعر العربي بنيجيريا: ولايتا هوسا ويوربا أنموذجين - Ahmad H.Osman, Rahmah; abdullahi, Mohamad Jamiu (Arab Organization for Translation, Lebanon, 2015)
Arabic poetry, for its well-established history in Nigeria, has always been of paramount importance to the Nigeria Arabic poets because of its cultural and religious purposes. As a result of its high demand among the preceding, and the eventful activities of the succeeding scholars, its beauty has remained a sparkling lustre, and continued to cope with the waves of life. Nigeria is a country naturally divided into three regions; the north and east, and south. Each region with its language and customs that provide link among its members, and at same time, distinguish it from the other. Majority of Nigerian Arabic poets, till date, remain predominantly in the two regions, north and south largely because of Islam and Muslims strength in the areas. Their strategic locations have created a stark difference in the emergence of Islam and Arabic language, hence the evolution Arabic poem in both. It's on this fact that this article attempts a historical study of the emergence and development of Arabic poetry in both regions whose inhabitants are Hausa and Yoruba tribes.